An Analytical Study of Visual Illustrations in ‎Chemistry Textbooks for the Basic Stage in ‎Jordan in Light of Educational Standards - Nwafleh, Waleed (Jordan Journal of Educational Sciences, 2023)
The purpose of this study was to determine the percentage of visual illustrations in elementary chemistry textbooks that meet educational standards and the degree to which they vary by grade level (ninth and tenth). To achieve the objectives of the study, an analysis form was designed to analyze the pictures, graphics, tables, and charts. It consisted of 20 criteria distributed over five domains: realism; accuracy, clarity, and color; related to objectives and content; size and density; and consideration for learners. The results indicated that the general average of the percentage of verification of educational standards for the illustrations as a whole in the chemistry textbook for the ninth grade was 94.1%, with a high degree, and the standards ranged between 79% and 100%.. In the tenth grade textbook, the general average of the percentage of verification of educational standards for the illustrations as a whole was 92.8 percent with a high degree, and the standards ranged between 76% and 100%..The percentages of domains that have been verified in the two textbooks are ordered as follows: The domains of realism, association with aims, size and density, accuracy, clarity, and color, and finally the domain of learner consideration, all with high degrees.The results also revealed that there was no statistically significant difference in the percentage of verification of the educational standards for the visual illustrations as a whole between the ninth and tenth grade textbooks. At the level of domains, there were significant differences between the two textbooks in the field of consideration for learners in favor of the ninth grade textbook. However, there were significant differences in five criteria at the level of standards. Three criteria were in favor of the ninth grade, namely: (the title fits with the illustration, is linked to the learner’s previous experiences, and gives the learner positive attitudes), and two criteria were in favor of the tenth grade, namely: (achieving all aims related to the concept, the illustration’s density of concepts and information is appropriate)